Students’ Perception of Using Randall’s ESL Cyber Listening Lab in the Interpretive Listening Class - Delsa Miranty (Journal of English Language Studies, 2017)
This present study aims to explore the students’ perception of applying Randall’s ESL cyber listening lab in the interpretive listening class. To do so, 40 students in the second semester in a state university at Banten provience, Indonesia, took part in this study. This research implemented qualitative research method. Then the data analysed by using descriptive statistics. Data taken from questionnaire that distributed to 40 students. The questions in the questionnaire sheet consists of ten questions and divided into three part in order to achieve the maximum results about the students’ perception of using Randall’s ESL cyber listening lab. The results showed that option yes was chosen by most of the students as the samples of this study. It means that the students were agree that Randall’s ESL cyber listening lab gave positive effects in the teaching learning process in the language laboratory and can be used as one of the source in the listening class that make the listening class interesting and challenging. Moreover, Randall’s ESL cyber listening lab is really recommended for other teachers and students who want to learn listening in and out of the class room since in this research the students’ gave positive perception after applied the Randalls’ ESL cyber listening lab. Keywords: Listening Class; Randalls’ ESL Cyber Listening Lab; Students’ Perception